Efficacy of Terminalia arjuna (Roxb.) bark extracts against Salmonella sp. isolated from aquaculture ponds - Islam, Sohidul; Saha, Kartik Chandra; Sultana, Naima; Rahman, Md Raimur; Raihan, Johir; Farjana, Kaniz; Raihan, Rakiba Binta; Tabassum, Tamanna; Acharjee, Sourav; Shovon, Shadman Shakib; Nibir, Salman Shahriar; Kubra, Khadiza Tul; et al. (Research in Agriculture Livestock and Fisheries, 2024)
The present study was conducted to determine the efficacy of Terminalia arjuna bark extracts against Salmonella sp. isolated from 15 aquaculture ponds located adjacent to Bangladesh Agricultural University, Mymensingh. T. arjuna barks was dried, powdered and extracted using cold water (polar) and hexane (non-polar) and stored at 10ºC while Salmonella sp. were isolated using SS (Salmonella Shigella) Agar and selected 2 isolates were confirmed by Hi Assorted biochemical test kit. Antimicrobial activities of the bark extract of T. arjuna against fifteen selected isolates of Salmonella were then determined. Two of those selected isolates (Sa-2 and Sa-5) shown zone of inhibition against crude bark extract (hexane extract) of T. arjuna. The isolates were also screened for antibiotic resistance to eleven antibiotics. Salmonella isolates were serotyped and the antimicrobial resistance was determined by a disk diffusion method. About 100% of the isolates were resistant to antibiotic discs among which ampicillin (10 μg), and chloramphenicol (30 μg) showed 15%, azithromycin (10 μg) showed 45%, erythromycin (15 μg) showed 60%, tetracycline (10 μg) showed 40%, ampicillin (10 μg) showed 100%, doxycycline (30 μg) showed 46.67%, kanamycin (30 μg) and gentamycin (10 μg) showed 6%, streptomycin (25 μg) and ciprofloxacin (10 μg) showed 20%, and cefotaxime (30 μg) showed 30% resistant to isolated Salmonella sp. and all Salmonella sp. isolates were found to be 100% resistant to cold water extract but sensitive to hexane extract of T. arjuna. The study showed hexane extract of T. arjuna would be potential, ecofriendly and biodegradable herbal medicine to control multi drug resistant Salmonella sp. as well as aquaculture health management. Res. Agric. Livest. Fish. Vol. 11, No. 2, August 2024: 255-269